Protecting Healthcare Workers Amid the COVID-19 Crisis: A Safety Protocol in Wuhan - Liu, Yunlu; Yang, Shijun; Hung, Man; Tong, Wei; Liu, Yong (Frontiers in Public Health, 2020)
Coronavirus disease 2019 (COVID-19), which is caused by a distinct coronavirus, is an acute infectious disease that spreads mainly via the respiratory route. During the COVID-19 outbreak, many healthcare systems faced a severe burden when a large number of healthcare workers (HCWs) became infected due to the lack of adequate protection. Consequently, it was apparent that it is important to ensure the health and safety of HCWs in order to control the outbreak throughout society. In this article, we share our successful protocol for protecting the safety of HCWs in the course of their daily work in an orthopaedics department with the aim of eventually reducing the risk of nosocomial infection. None of our HCWs or their families contracted the infection during the COVID-19 pandemic.